Designing a Play-Based, Skill-Oriented Homework Model in the Persian Language Curriculum for Early Primary Education - Lirawi, Mahin; Saadatmand, Zohreh; Rahmani, Jahanbakhsh (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to design a play-based, skill-oriented homework model within the Persian language curriculum for early primary education. Methodology: Employing an exploratory mixed-methods design, this research was conducted in two phases. In the qualitative phase, thematic analysis was applied to analyze a corpus of educational documents, policy texts, and theoretical sources published between 2009 and 2024, retrieved using purposive sampling from credible academic and institutional databases. Data collection was conducted via inductive note-taking, and analysis followed a three-stage coding process (open, axial, and selective coding) based on the Attride-Stirling (2001) framework. The extracted themes were then validated using Lawshe's content validity ratio and Holsti’s intercoder reliability coefficient. In the quantitative phase, a researcher-made questionnaire was administered to a panel of educational experts to confirm the relevance and clarity of the derived components. Findings: The final model comprises four overarching components: homework objectives, homework design, homework implementation strategies, and homework evaluation. These were further divided into 33 organizing themes and 269 validated basic themes. The objectives of homework covered eight domains including skill development, empowerment, social and emotional development, purposeful personal development, cognitive development, practical learning, and thinking development. Homework design included seven factors such as planning, context preparation, teacher roles, textbook content, assignment content, learning environment, and individual factors. Implementation strategies included motivational, collaborative, creativity-based, activity-based, research-based, and play-based methods. Evaluation methods encompassed formative, oral, and written assessments. Conclusion: The proposed model integrates developmental principles and culturally responsive pedagogy, offering a structured yet flexible approach to designing meaningful homework that fosters holistic learning in young students.